2006
DOI: 10.1021/bi0522293
|View full text |Cite
|
Sign up to set email alerts
|

Structural Differences in Triosephosphate Isomerase from Different Species and Discovery of a Multitrypanosomatid Inhibitor

Abstract: We examined the interfaces of homodimeric triosephosphate isomerase (TIM) from eight different species. The crystal structures of the enzymes showed that a portion of the interface is markedly similar in TIMs from Trypanosoma cruzi (TcTIM), Trypanosoma brucei, and Leishmania mexicana and significantly different from that of TIMs from human, yeast, chicken, Plasmodium falciparum, and Entamoeba histolytica. Since this interfacial region is central in the stability of TcTIM, we hypothesized that it would be possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 22 publications
2
60
0
2
Order By: Relevance
“…We examined the interface of TIM from three different trypanosomatids, T. cruzi, Trypanosoma brucei (TbTIM) and Leishmania mexicana (LmTIM) and five other species, yeast, chicken, Homo sapiens (HsTIM), Plasmodium falciparum and Entamoeba histolytica. Our data shows that the structure of this portion of the interface is highly conserved in the enzymes from the trypanosomatids (TcTIM, LmTIM and TbTIM), differing from the other analyzed species 8 . In fact, the identity of the 32 interfacial residues of TcTIM, TbTIM and LmTIM with the homology of HsTIM is approximately 52 %.…”
Section: Research Articlementioning
confidence: 70%
See 1 more Smart Citation
“…We examined the interface of TIM from three different trypanosomatids, T. cruzi, Trypanosoma brucei (TbTIM) and Leishmania mexicana (LmTIM) and five other species, yeast, chicken, Homo sapiens (HsTIM), Plasmodium falciparum and Entamoeba histolytica. Our data shows that the structure of this portion of the interface is highly conserved in the enzymes from the trypanosomatids (TcTIM, LmTIM and TbTIM), differing from the other analyzed species 8 . In fact, the identity of the 32 interfacial residues of TcTIM, TbTIM and LmTIM with the homology of HsTIM is approximately 52 %.…”
Section: Research Articlementioning
confidence: 70%
“…As part of our ongoing program in the search of molecules that could provide leads in the design of a new drug for the treatment of Chagas disease 8,9,11 , we undertook a massive screening for inhibitors of TcTIM, using nearly 230 compounds from an in-house library 12 . We identified two compounds (1 and 2, Figure 1), belonging to the 1,2,4-thiadiazol and 1,3,4-oxathiazol chemotypes, that displayed selectivity for TcTIM over HsTIM.…”
mentioning
confidence: 99%
“…We examined the interface of TIM from three different trypanosomatids, T. cruzi, Trypanosoma brucei (TbTIM) and Leishmania mexicana (LmTIM), and five other species, yeast, chicken, Homo sapiens (HsTIM), Plasmodium falciparum and Entamoeba histolytica. Our data show that the structure of the interface is highly conserved in the enzymes from the trypanosomatids (TcTIM, LmTIM and TbTIM), and differs significantly from that of the other species analyzed 8 . In fact, the identity of the 32 interfacial residues of TcTIM, TbTIM and LmTIM with the homologous HsTIM is approximately 52%.…”
Section: Introductionmentioning
confidence: 70%
“…The potential use of protein-protein interfaces of homodimeric enzymes, as targets for drug discovery, has been reviewed 10 . As part of our ongoing program in the search of molecules that could provide leads in the design of a new drug for the treatment of Chagas disease 8,9,11,12 , we undertook a large screening for inhibitors of TcTIM, using nearly 230 compounds from an in-house chemical library 13 . We identified four compounds (1-4, Figure 1), belonging to the 1,2,4-thiadiazole, phenazine and 1,2,6-thiadiazine chemotypes, that displayed selectivity for TcTIM over HsTIM.…”
Section: Introductionmentioning
confidence: 99%
“…The triose phosphate isomerase (TIM) is also a central enzyme of the glycolytic pathway that has been studied in T. cruzi and in a number of pathogenic protozoa (Pérez-Montfort et al 1999, Reyes-Vivas et al 2001, Rodríguez-Romero et al 2002, Olivares-Illana et al 2006. Recently, two studies showed the possibility of developing new therapeutic agents against trypanosomes using TIM as a molecular target.…”
Section: The Energy Metabolismmentioning
confidence: 99%